The role of the library in developing information literacy and life-long learning skills - Lasić-Lazić, Jadranka; Slavić, Aida (1999)
The paper will summarise both existing and potential functions the library will provide in the information society. Traditional and modern information skills will be considered along with the impact they have in a technologically changed environment. The paper will try to explain the impact a modern library could have on the information society (and vice versa). Special emphasis is placed on the role the library has in developing users' information skills, and on being an environment for lifelong learning.
The changes brought about by the information society influence both the information and education needs of the individuals. Rapid technological change has imposed demands that an individual can only satisfy by developing skills for lifelong learning. Schools are more likely to be placed where the learning process itself will be taught, whereas the library will be placed where learning will take place. This will influence the competencies library professionals will need in order to anticipate users' demands. The authors will try to summarise the services a modern library will offer and the librarianship skills it will require. The difference between highly developed and developing countries will be underlined.
Projekt MZOS
ENG